Development of AI-Based Cartoon Media with Cianjur Tauco Local Wisdom Context to Improve Mathematical Understanding of Elementary School Students - Nia Jusniani; Rani Sugiarni (Journal of Educational Studies, 2025)
Low mathematical understanding among elementary school students in Indonesia is a pressing problem, as National Assessment data show that only 28.7% of elementary students achieve adequate numeracy competence. One primary cause is the scarcity of contextual, innovative learning media capable of connecting abstract mathematical concepts to students' lived experiences. This study develops an Artificial Intelligence (AI)-based cartoon medium set within the Cianjur tauco local wisdom context to improve the mathematical understanding of fourth-grade elementary students. The method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Sixty fourth-grade students of SDN Pasarsuuk, Cianjur Regency, participated—32 in the experimental group (class IVA) and 28 in the control group (class IVB)—selected through purposive sampling. Research instruments included expert validation sheets, practicality observation sheets, student response questionnaires, and mathematical understanding tests in pre-test and post-test form. Results showed a mean validity score of 3.78 (very valid), a mean practicality score of 3.75 (very practical), and positive student responses of 87.5%. The class average rose from 58.40 to 79.20, with an N-Gain of 0.49 (moderate) and a mastery rate of 81.3%. The novelty of this study lies in simultaneously integrating generative AI technology, visual-narrative cartoon format, and Cianjur tauco local wisdom into a single contextual, meaningful, and culturally grounded mathematics learning media product.